Detection of tmprss2-erg and tmprss2-egr1 gene fusion in prostate cancer from a Chinese population - Changqing Xu; Jindan Luo; Mengmeng Wang; Yin Wang; Zhaojing Chen; Yifei Cao; Yu Hong; Xianrong Xu; Jun Yang (Egyptian Journal of Medical Human Genetics, 2020)
Abstract Background TMPRSS2: ETS gene fusion occurs recurrently in a high proportion of prostate cancer (PCa) patients in Western countries. However, for Chinese PCa patients, no solid conclusion could be drawn from the present studies, as the results varied considerably between the limited reports. Results In this study, we evaluated the prevalence of such gene rearrangements in a small number of Chinese PCa patients and discovered that 6 out of 27 (22.2%) were found to harbor the TMPRSS2: ERG fusion, the ratio was much lower than that in Western countries. Furthermore, we first identified TMPRSS2: EGR1 gene fusion, suggesting other chromosome rearrangements besides ETS gene family harbor in prostate cancer. The hybrid transcript was predicted to encode a truncated EGR1 protein by ORF finder, which might play a key role in prostate cancer. Conclusions We reported that the total occurrence rate of TMPRSS2: ERG fusion gene in this small group of Chinese patients was lower than the reported frequencies in European descent patients but comparable to other reported frequencies in Asian populations. The occurrence of TMPRSS2: EGR1 gene fusion suggested other chromosome rearrangements in prostate cancer.